The impact of work related factors on academic librarians' occupational commitment - Dadi, Mohammed Suleiman (Kulliyyah of Information and Communication Technolog, yInternational Islamic University Malaysia, 2014)
The work of academic libraries is currently facing contentious changes (technology changes, economic turmoil, and global competitions) that need continuous up-to-date qualifications and skills for one to remain employable through one's tenure. Occupational commitment has direct link to the whole organisation's effectiveness, turnover, productivity, performance, absenteeism, etc. One way to discover the importance of workforce in the academic libraries is to examine the employees' levels of commitment. Commitment has been a construct that has attracted researchers of different disciplines. Unfortunately, libraries and more specifically academic libraries have not received that much attention. The current study explored the levels of occupational commitment on librarians as well as the impact of job satisfaction, job involvement, perceived fairness, kaizen, and ethics on the levels of occupational commitment. Furthermore, the study examined the correlation of job satisfaction, job involvement, perceived fairness, kaizen, ethics, gender, age, tenure, and education with occupational commitment. The study used Meyer and Allen's (1991 and 1997) Three-Component Model. A total of 126 academic librarians working in (Dar- es-salaam, Morogoro, and Zanzibar) academic libraries responded to self-administered questionnaires. The results showed that Tanzania academic librarians have high levels of occupational commitment. The continuance occupational commitment scored the highest level followed by normative and then the affective. The results of independent sample t-tests showed that there were significant differences for males and females (job satisfaction, job involvement, perceived fairness, ethics, and kaizen). Likewise, the t-tests showed statistically significant differences between gender at affective and continuance occupational commitment. The research has shown that Tanzanian academic librarians have significant mean differences in education, age, and tenure. Correlations results showed that job satisfaction was highly correlated with continuance, normative, job involvement, perceived fairness, kaizen, and ethics. However, job satisfaction moderately correlated with affective occupational commitment. Besides, results showed that job satisfaction, job involvement, perceived fairness, kaizen, and ethics could significantly contribute towards variance in occupational commitment. Multiple regression results revealed that perceived fairness was the best predictor in occupational commitment followed by job involvement, job satisfaction, ethics, and kaizen. Job satisfaction was the best predictor of all the occupational commitment components, followed by job involvement, and kaizen. Some of the limitations of the study were due to limited number of respondents that affected the effect size on the results as well as on generalization. In addition, problems facing librarians are many, and it is impossible to precisely identify which problems are more pressing than the others. Due to time constraints and limited budget the study could not involve every qualified librarian in the country. Besides, problem of confounding variables might have been overlooked. And lastly, there might be other possible factors which are not known to the researcher.